Leksikon dalam Pernikahan Adat Jawa Kecamatan Trowulan, Kabupaten Mojokerto: Kajian Etnolinguistik - Amilatus Sholikah; Falah Arifbillah Subagio; Taswirul Afkar (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to describe and analyze the lexicon used in traditional Javanese wedding ceremonies in Trowulan District, Mojokerto Regency, through an ethnolinguistic approach. The lexicon is not merely a set of communicative terms, but also conveys cultural values such as sacredness, harmony, and reverence for ancestors. The research employs a descriptive qualitative method with data collected through participatory observation, in-depth interviews, and documentation of cultural symbols. The findings reveal that lexicons such as siraman, midodareni, temu manten, kembar mayang, and sungkeman carry symbolic meanings that reflect the value system of Javanese society. These lexicons not only reinforce local cultural identity but also function as a medium for transmitting traditions. This study emphasizes the importance of preserving traditional lexicons as a form of cultural heritage and offers valuable insights for the advancement of linguistic and cultural studies in Indonesia.)